2015
DOI: 10.1182/blood-2014-08-596247
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling identifies two splenic marginal zone lymphoma subgroups with different clinical and genetic features

Abstract: Key Points• Methylation profiling identifies subgroups of SMZL with distinct biological features.• Demethylating agents can reverse some of the adverse epigenetic alterations.Splenic marginal zone lymphoma is a rare lymphoma. Loss of 7q31 and somatic mutations affecting the NOTCH2 and KLF2 genes are the commonest genomic aberrations. Epigenetic changes can be pharmacologically reverted; therefore, identification of groups of patients with specific epigenomic alterations might have therapeutic relevance. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 50 publications
(63 reference statements)
2
66
0
Order By: Relevance
“…For SMZLs, the frequency of the histologic transformation of varies from 5% to 19% [47,12,13]. A recent retrospective study reported an incidence rate of 5% for histological transformation in a large series of 85 SMZL patients, whose median follow-up time was 4.8 years [6].…”
Section: Discussionmentioning
confidence: 99%
“…For SMZLs, the frequency of the histologic transformation of varies from 5% to 19% [47,12,13]. A recent retrospective study reported an incidence rate of 5% for histological transformation in a large series of 85 SMZL patients, whose median follow-up time was 4.8 years [6].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been done in hopes of finding exactly which genes and pathways are altered in SMZL, therefore serving as potential targets on the development of SMZL murine models. A summary of these studies can be found in Table 1 (8, 9, 11, 1315, 1725). Although many genes (most notably NOTCH2, KLF2, KLF4, and BIRC3) have been reported as mutated in SMZL, we suggest that the 7q deletion is of primary importance, as it is possible this deletion serves as a marker for disease progression and may even be a causative event, rather than a pro-survival function as was previously speculated (9).…”
Section: Possible Contributing Factors Leading To Tumorigenesismentioning
confidence: 99%
“…In a genome-wide DNA-promoter methylation profiling study by Arribas et al, two main clusters were distinguished based on the degree of promoter DNA methylation (15). This high-M cluster not only had an inferior outcome and showed high risk for histologic transformation to DLBCL but suggests that DNA hypermethylation could act together with 7q31-32 deletion, NOTCH2 mutation, and IGHV1-02, to determine a distinct genetic and epigenetic subgroup of SMZL (11).…”
Section: Possible Contributing Factors Leading To Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…1 In this edition of Blood, Arribas et al show that DNA methylation profiling identifies 2 subtypes of splenic marginal zone lymphoma with different clinical and genetic features. 2 These findings provide an opportunity to better understand the biology of marginal zone lymphoma and optimize therapy by using demethylating agents to reverse the high-methylation phenotype and thereby target malignant B cells. S plenic marginal zone lymphoma is an uncommon B-cell malignancy representing ;8% of all non-Hodgkin lymphomas.…”
Section: Dna Methylation In Lymphoma: An Opportunity? ---------------mentioning
confidence: 99%